Production of Biomethanol from Renewable Resources A Life Cycle Assessment with Incorporation of Biodiversity - Rydin, Linnéa; Svensson, Victoria (My University, 2022)
There is growing interest in society for mitigating climate change and sustaining bio- diversity. It becomes more and more important for society and companies to produce sustainable products that has a low environmental impact. Renewable resources from the forest is being presented as a more sustainable option to fossil resources and is playing an important role in for example EU’s future strategies to achieve climate neutrality. It is of importance to produce these forest resources in a sustainable way and assessing the en- vironmental performance is an important tool to achieve a sustainable production. One big stakeholder regarding products made from renewable forest resources in the south of Sweden is the forestry industry group Södra Skogsägarna Ekonomisk Förening, which recently installed a new production facility at their paper pulp mill in Mönsterås to be able to utilize the by-product biomethanol. This project aimed at investigating how the production of Södras biomethanol impacts the environment and this was achieved by performing an attributional cradle to gate LCA. The purpose was also to investigate how the biomethanol production impacts biodiver- sity and what type of methods for assessing biodiversity that can be used and included in the LCA. To assess the impact on biodiversity, two methods were used. A method developed by Chaudhary et al., (2015) was used for assessing biodiversity on a species level and another method by Lindner et al., (2021) was used for an ecosystem perspective. The results showed an environmental impact from the production of biomethanol. Espe- cially the results from the impact category of global warming potential (GWP) was lower compared to fossil-based methanols. The methods for including biodiversity in LCA were concluded to have both advantages and disadvantages in assessing the biodiversity im- pact of Södra’s biomethanol production. The results regarding biodiversity showed an impact of the same magnitude as comparative data from scientific articles using the same methods, but the results were difficult to analyse due to the methods not being widely used in similar LCA’s.
Keywords: Life Cycle Assessment; Biodiversity; Biodiversity in LCA; Forestry; Biomethanol; Methanol; Renewable resources